Respuesta :

Answer:

[tex] x = \dfrac{-\log 7}{\log 7 - \log 2} [/tex]

Step-by-step explanation:

[tex] 2^x = 7^{x + 1} [/tex]

Take the log of both sides.

[tex] \log 2^x = \log 7^{x + 1} [/tex]

Use properties of log.

[tex] x \log 2 = (x + 1) \log 7 [/tex]

[tex] x \log 2 = x \log 7 + \log 7 [/tex]

[tex] x \log 2 - x \log 7 = \log 7 [/tex]

[tex] x(\log 2 - \log 7) = \log 7 [/tex]

[tex] x = \dfrac{\log 7}{\log 2 - \log 7} [/tex]

[tex] x = \dfrac{\log 7}{-(\log 7 - \log 2)} [/tex]

[tex] x = \dfrac{-\log 7}{\log 7 - \log 2} [/tex]